Modern Urban Culture: a City for or against a Person? - O. V. Kireeva; M. N. Veselova (Дискурс)
Introduction. The paper attempts to find answers to the questions: will it be possible to preserve historical-cultural “face” of the city, or it will disappear under the onslaught of the advanced achievements of civilization; is there an urban space to a reasonable person, who have reached great technological heights, or directed against him; what are the ontological foundations of the modern city? The relevance of the author's approach is the analysis of the “concept” of the city as urogenous spatio-temporal macro model, which not only develops under the influence of the inhabitants, but also determines their worldview and behavior.Methodology and sources. Methodological basis of the work is the cultural and philosophical analysis of the “concept“ of the modern city in the works of domestic and foreign sociologists, and ethologists, urboecology, philosophers, anthropologists, art historians (V. G. Il’in, R. Park, L. Worth, E. Gorokhovskaya, I. A. Litvinova, V. I. Mathis, G. Simmel, E. Fromm, E. T. Hall, M. I. year-old boy, James W., Jean-Paul Ferrier, Jean-Albert Guieysse, Thierry Rebour, H. W. Zorbaugh, etc.). Used demographic statistics allowing to understand the issues of depopulation, migration and multi-ethnicity of the townspeople.Results and discussion. In modern culture hypertrophied original function of the city as a source of protection and comfort, it is a shift towards maximum convenience and independence of individuals. In the result, the urban environment is made, adapting to the challenges put forward by society. Historically “face” of the city gets lost. This jeopardizes not only the rich cultural heritage of the cities, but also the authenticity of the existence of the person. The ontological basis of the modern “concept” of the city is defined by urban characteristics: multiculturalism, multi-ethnicity, presentationhost (the image of the city), the superficiality of contact, the spontaneity of development, the blurring of boundaries. They not only make up the text of modern urban culture, but also form a macro model of society.Thus, the result of the study is the conceptualization of the contradictions of the modern city that provides for a person as comfortable as possible in the consumer environment at the same time directed against him or her.Conclusion. It is concluded that in the current ecological, demographic and economic situation, the question of understanding the role of modern urban culture in the search for a dialogue between the technogenic and informational development of civilization with nature, the historical and cultural content of the city with its image, and mass consumption with an original manifestation is most acute. The authors believe that it depends only on the person whether the urban space will exist for or against him or her.